2018
DOI: 10.1194/jlr.m085209
|View full text |Cite
|
Sign up to set email alerts
|

Increased FGF21 in brown adipose tissue of tyrosine hydroxylase heterozygous mice: implications for cold adaptation

Abstract: are likely due to compensatory mechanisms involving elevations in Fgf21 and Prdm16 and through adaptive changes in the lipid profile.-Vázquez, P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…It has been found that FGF21 can enhance energy consumption by regulating the expression of thermogenic genes in adipose tissues such as BAT and subcutaneous WAT, thus reducing blood glucose and lipid levels and ameliorating glucose tolerance and insulin resistance in obese and diabetic mice [ 109–111 ]. Under long-term cold exposure, FGF21 expression in both BAT and subcutaneous WAT of mice increased significantly [ 112 , 113 ]. Under cold exposure conditions, FGF21 significantly enhances PGC-1α protein levels, and enables PGC-1α to participate in thermogenesis of adipose tissue induced by FGF21 [ 114 ].…”
Section: Fibroblast Growth Factor 21mentioning
confidence: 99%
“…It has been found that FGF21 can enhance energy consumption by regulating the expression of thermogenic genes in adipose tissues such as BAT and subcutaneous WAT, thus reducing blood glucose and lipid levels and ameliorating glucose tolerance and insulin resistance in obese and diabetic mice [ 109–111 ]. Under long-term cold exposure, FGF21 expression in both BAT and subcutaneous WAT of mice increased significantly [ 112 , 113 ]. Under cold exposure conditions, FGF21 significantly enhances PGC-1α protein levels, and enables PGC-1α to participate in thermogenesis of adipose tissue induced by FGF21 [ 114 ].…”
Section: Fibroblast Growth Factor 21mentioning
confidence: 99%
“…The liver and the AT secrete it in endocrine, paracrine and autocrine ways. Fgf21 is a crucial gene in BAT activation and browning of WAT [ 42 , 43 ]. It stimulates PPAR-γ activity and PGC1-α expression, and enhances UCP1 production, increasing the thermogenic activity in beige and brown cells [ 42 , 44 , 45 ].…”
Section: Thermogenic Adipose Tissuementioning
confidence: 99%
“…FGF21 and adiponectin are two identified molecules with an atheroprotective behavior released by activated BAT ( Figure 3 ), and their potential systemic and local anti-atherogenic effects have been suggested [ 110 ]. FGF21, in addition to its thermogenic implication in beige and brown cells, has several metabolic functions [ 42 , 43 ]. It stimulates PPAR-γ activity and adiponectin expression, increases lipid and glucose uptake and improves lipid profile by suppressing the nuclear sterol regulatory element binding protein-1, a hepatic factor involved in the biosynthesis of cholesterol [ 111 ]; in particular it leads to a decrease of triglyceride and LDL levels and an increase of HDL levels [ 97 , 111 ].…”
Section: Atherosclerosismentioning
confidence: 99%
“…Administration of FGF21 lowered plasma triglycerides in mice through reduced hepatic very low-density lipoprotein secretion and increased lipoprotein disposal in adipose tissue (Schlein et al 2016). FGF21 and PRDM16 have been reported to compensate for the reduced sympathetic response to cold exposure in a tyrosine hydroxylase haplodeficient mouse model suggesting a mechanism independent of the classic adrenergic pathway (Vazquez et al 2018). In humans, circulating FGF21 correlated with brown fat activity determined by FDG uptake in PET/CT studies and in human brown adipocytes FGF21 and FNDC5 had additive effects on norepinephrine-stimulated thermogenesis (Lee et al 2014a, Hanssen et al 2015a.…”
Section: Exercise and Browningmentioning
confidence: 99%